The changes in placental IL-10 level, placental IFN-y level, and placental VCAM-1 expression in endothelial dysfunction model using Mus musculus which had mild regular exercise - Noor, Meitria Syahadatina (SAGE Publications Inc, 2018)
Preeclampsia is a syndrome that consists of hypertension (blood pressure⩾140/⩾90mmHg) and proteinuria (⩾0.3g/24h). It occurs after 20weeks of gestation. Preeclampsia and eclampsia are the causes of maternal mortality in Indonesia. Hypertension is the second cause of maternal mortality in Indonesia after hemorrhage. The mechanism of preeclampsia might occur through inflammation process that would cause endothelial dysfunction. Preeclampsia leads to complications both in the mother and the fetus. The effective management for preeclampsia is prevention, including mild regular exercise since early pregnancy. This research objective was to analyze the inflammation process and endothelial dysfunction in an endothelial dysfunction model using mice who had mild regular exercise since early pregnancy. There were three treatment groups with 14 mice each, namely, normal pregnancy group (K1), endothelial dysfunction group (K2), and endothelial dysfunction group with mild regular exercise since early pregnancy (K3). The mice in K3 group had mild regular exercise by doing a treadmill for 18min once every 2days. The results showed that the placental interleukin 10 (IL-10) level in K3 was lower than that in K2 (599.86 vs 636.36, P=0.001), the placental interferon gamma (IFN-γ) level in K3 was higher than that in K2 (322.36 vs 299.50, P=0.002), and the placental vascular cell adhesion molecule 1 (VCAM-1) expression in K3 was higher than that in K2 (5.33 vs 1.67, P=0.000). It can be concluded that mild regular exercise since early pregnancy did not decrease the inflammation process and the expression of placental VCAM-1 in endothelial dysfunction model using mice. Keywords endothelial dysfunction, mild regular exercise, placental inflammation, preeclampsia